Nanomaterials for good indoor environments: electrochromics, sensors and photo-catalysts - Granqvist, Claes-Göran (2012)
Nanomaterials can be used in a number of technologies in order to create good indoor environments. This paper takes a unified view on this issue from a solar-energy-based perspective and specifically considers electrochromics for achieving good day-lighting jointly with energy efficiency, sensors aimed at air quality assessment, and photo-catalysis for air cleaning. Recent results, mainly from the author’s laboratory, are reported for all of these areas. Work performed by PhD students and other collaborators from Peru are highlighted.